Preparation method of high-sulfur high-acid crude oil demulsifier

Through the combined use of modified polyether, zwitterionic surfactant and activated alumina, the problem of difficult emulsification system in high-sulfur and high-acid crude oil is solved, and efficient crude oil demulsification and equipment protection are achieved.

CN119709249AActive Publication Date: 2025-03-28ZIBO KAIMEIKE IND & TRADE CO LTD

Patent Information

Application Number
CN202510240547.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-03
Publication Date
2025-03-28
Estimated Expiration
2045-03-03

AI Technical Summary

Technical Problem

The emulsification system in high-sulfur and high-acid crude oil is difficult to demulse, mainly due to the stable interface film formed by cycloalkane acid, asphaltene and gum, and the enhanced interface stability of sulfide precipitation, which makes it difficult for water droplets to aggregate.

Method used

Modified polyether and zwitterionic surfactant are used to combine activated alumina, antacid and corrosion inhibitors to reduce the surface tension of the oil-water interface through synergistically, and promote the aggregation and separation of oil and water droplets.

Benefits of technology

It significantly improves the demulsification efficiency of high-sulfur and high-acid crude oil, enhances the treatment efficiency of acidic substances, maintains the stability of the demulsification system, and provides multiple protections to prevent equipment corrosion.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention relates to the technical field of petrochemical engineering, and particularly discloses a preparation method of a high-sulfur and high-acid crude oil demulsifier, which comprises the following steps: uniformly mixing 40-60 parts by mass of modified polyether, 25-30 parts by mass of zwitterionic surfactant and 10-12 parts by mass of solvent, heating to 50-70 DEG C, reacting for 1-2 hours, and cooling to room temperature to obtain the high-sulfur and high-acid crude oil demulsifier. Adding 3-8 parts by mass of activated aluminum oxide, 8-16 parts by mass of an antacid and 2-4 parts by mass of a corrosion inhibitor, uniformly mixing, adding 0.5-1 part by mass of a defoaming agent, uniformly mixing, cooling, and standing for layering to obtain a demulsifier; the antacid comprises ethanolamine and zinc oxide. The demulsifier prepared by the invention not only has excellent performance in the aspects of dehydration and promotion of oil-water separation, but also can improve the quality of crude oil and reduce the acid value and the sulfur content to a certain extent.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of petrochemical technology, and more specifically, to a method for preparing a high-sulfur and high-acid crude oil demulsifier. Background Art

[0002] High-sulfur and high-acid crude oil refers to crude oil with a sulfur content higher than 2% (mass fraction) and an acid value (measured in KOH) greater than 1.0 mg / g. In this type of crude oil, sulfur mainly exists in the form of inorganic sulfur (such as hydrogen sulfide) and organic sulfur compounds (thiols, sulfides, thiophenes, etc.), while the acidic substances in crude oil are mainly composed of cyclohexane acids.

[0003] In the emulsion system formed by high-sulfur and high-acid crude oil, demulsification faces many severe challenges. Due to the interaction of active ingredients such as cyclohexane acid, asphaltene and some colloids, a tough and stable interfacial film is formed at the oil-water interface, making it difficult for water droplets to coalesce, making demulsification extremely difficult. At the same time, the presence of substances such as hydrogen sulfide not only makes the crude oil highly corrosive, but also reacts chemically with metal ions in the water phase to generate various sulfide precipitates. These sulfide precipitates may adhere to the oil-water interface or the surface of water droplets, further enhancing the stability of the interfacial film, or changing the charge characteristics of the surface of water droplets, thereby increasing the difficulty of demulsification. In addition, organic sulfur compounds have certain surface activity. They can be adsorbed at the oil-water interface and work together with other emulsifiers in crude oil (such as cyclohexane acid) to form a more stable interfacial film. Moreover, as the extraction, transportation and storage time of crude oil are prolonged, further chemical reactions may occur between the components in the crude oil, resulting in a more complex and changeable emulsification system, which places higher requirements on the performance and adaptability of demulsifiers.

[0004] The patent application document with publication number CN103374386A discloses a composite demulsifier, which is a solution, comprising, by mass: 5 to 60 parts of polyoxyethylene polyoxypropylene block polyether; 2 to 10 parts of primary amide; 1 to 20 parts of C2 to C6 carboxylic acid and 20 to 90 parts of water; the primary amide is one or more of C2 to C6 fatty amide and niacinamide.

[0005] When the composite demulsifier prepared in the patent application is used for high-acid crude oil, C2~C6 carboxylic acids may interact with acidic components such as cyclohexane acid in the crude oil, which may further stabilize the acid film at the oil-water interface, resulting in poor demulsification effect. In addition, the carbon chain of carboxylic acids is relatively short (C2~C6), and their lipophilic properties are relatively limited. Their solubility in the oil phase and their affinity for the oil phase may not be sufficient to enable them to effectively play a role at the oil-water interface. Summary of the invention

[0006] In order to enhance the demulsification effect of a demulsifier in high-sulfur and high-acid crude oil, the present application provides a method for preparing a high-sulfur and high-acid crude oil demulsifier.

[0007] The present application provides a method for preparing a high-sulfur and high-acid crude oil demulsifier, which adopts the following technical scheme: A method for preparing a high-sulfur and high-acid crude oil demulsifier comprises the following steps: 40-60 parts by weight of modified polyether, 25-30 parts by weight of zwitterionic surfactant and 10-12 parts by weight of solvent are mixed evenly, heated to 50-70° C., 3-8 parts by weight of activated alumina, 8-16 parts by weight of antacid and 2-4 parts by weight of corrosion inhibitor are added, mixed evenly, 0.5-1 parts by weight of defoamer are added, mixed evenly, cooled, and allowed to stand for stratification to obtain a demulsifier; the antacid comprises ethanolamine and zinc oxide.

[0008] Preferably, 40 to 60 parts by mass of the modified polyether, 25 to 30 parts by mass of the zwitterionic surfactant and 10 to 12 parts by mass of the solvent are uniformly mixed at 30 to 40°C.

[0009] Preferably, the mass ratio of ethanolamine to zinc oxide is (5-10):(3-6).

[0010] Preferably, the zinc oxide particle size distribution is 50-100 nm.

[0011] Preferably, the corrosion inhibitor is oleic acid imidazoline.

[0012] Preferably, the particle size distribution of the activated alumina is 1-10 μm.

[0013] Preferably, the defoaming agent is a silicone rubber defoaming agent.

[0014] By adopting the above technical scheme, firstly, the modified polyether can quickly migrate to the oil-water interface and gradually arrange into an interfacial film, and the addition of zwitterionic surfactants can further enhance the stability and strength of the interfacial film, thereby effectively reducing the surface tension of the oil-water interface, and jointly promoting the aggregation and separation of oil droplets and water droplets through different mechanisms of action, thereby improving the demulsification efficiency.

[0015] Secondly, when activated alumina and antacids are used together, activated alumina can pre-absorb and remove some of the acidic substances in crude oil, reducing the content of acidic substances in crude oil, so that the antacid can more effectively neutralize the remaining acidic substances. The neutralization products formed may be further adsorbed by activated alumina, thereby preventing these products from re-dissolving in crude oil or interfering with the demulsification process. This synergistic effect not only improves the treatment efficiency of acidic substances, but also maintains the stability of the demulsification system. At the same time, the combined effect of activated alumina and antacids can also maintain the pH balance of the demulsifier system, thereby ensuring that the demulsifier can continue to work effectively.

[0016] Finally, the addition of corrosion inhibitors provides an extra layer of protection for metal equipment. Based on the effects of activated alumina and antacids, the protective film of the corrosion inhibitor is more durable and effective. Even when the activated alumina is saturated with adsorption or the antacid is exhausted, the corrosion inhibitor can still provide the necessary protection to prevent further corrosion damage to the equipment. This multiple protection system greatly enhances the durability and safety of the equipment.

[0017] Preferably, the solvent is toluene.

[0018] Preferably, the preparation method of the modified polyether comprises the following steps: S11: Under an inert atmosphere, polyethylene polyamine, catalyst A and solvent are mixed uniformly in a reactor, and the temperature is raised to 110-130° C., and then a portion of propylene oxide is added to the reactor in 4-6 times, and each time it is added, the reaction is carried out for 15-20 minutes; then a portion of ethylene oxide is added to the reactor, and the reaction is carried out for 60-90 minutes, and another portion of propylene oxide is added to the reactor in 2-4 times, and each time it is added, the reaction is carried out for 10-15 minutes, and then another portion of ethylene oxide is added to the reactor, and the temperature is raised to 120-140° C., and after reacting for 50-70 minutes, the temperature is lowered, distilled, and washed to obtain a polyether intermediate with a comb-shaped structure; S12: Under an inert atmosphere, the polyether intermediate, catalyst B, solvent and allyl sultone are uniformly mixed in a reactor, the temperature is raised to 90-110° C., the reaction is performed for 2-4 hours, the temperature is lowered, distilled and washed to obtain a modified polyether; The mass ratio of the polyethylene polyamine, propylene oxide and ethylene oxide is (15-20): (15-20): (60-70), and the amount of the allyl sultone is 5%-15% of the total mass of the polyethylene polyamine, propylene oxide and ethylene oxide.

[0019] Preferably, the catalyst A is potassium hydroxide, and the amount of potassium hydroxide used is 1% to 2% of the total mass of polyethylene polyamine, propylene oxide and ethylene oxide.

[0020] Preferably, the catalyst B is triethylamine, and the amount of the triethylamine used is 1% to 3% of the total mass of polyethylene polyamine, propylene oxide, ethylene oxide and allyl sultone.

[0021] Preferably, the polyethylene polyamine is at least one of diethylenetriamine and triethylenetetramine.

[0022] Preferably, in step S11, under an inert atmosphere, polyethylene polyamine, catalyst A and solvent are mixed uniformly in a reactor, the temperature is raised to 110-130° C., the pressure is 0.2-0.4 MPa, and then a portion of propylene oxide is added to the reactor in 4-6 times, and the reaction is carried out for 15-20 minutes after each addition; then a portion of ethylene oxide is added to the reactor and reacted for 60-90 minutes, and another portion of propylene oxide is added to the reactor in 2-4 times, and the reaction is carried out for 10-15 minutes after each addition, and then another portion of ethylene oxide is added to the reactor, the temperature is raised to 120-140° C., and the pressure is controlled at 0.3-0.5 MPa. After reacting for 50-70 minutes, the temperature is lowered, distilled, and washed to obtain a polyether intermediate with a comb-shaped structure.

[0023] By adopting the above technical scheme, a polyether intermediate with a comb-shaped structure and allyl sultone are further compounded to prepare a modified polyether. On the one hand, a sulfonic acid group is introduced into the polyether molecule, which can not only improve the chemical stability of the polyether in high-sulfur and high-acid crude oil, making it more resistant to the erosion of acidic components in crude oil, but also enhance the activity of the polyether at the oil-water interface, making it more effective in disintegrating the stable emulsion film constructed by the acidic components, and improving the demulsification effect. On the other hand, the zwitterionic surfactant can be filled between the polyether intermediate molecules to further enhance the stability of the interface film, and the synergistic effect between them can more effectively reduce the oil-water interfacial tension and improve the demulsification efficiency of crude oil.

[0024] Preferably, the method for preparing the zwitterionic surfactant comprises the following steps: The oleic acid, monomer A, solvent and antioxidant are mixed evenly, and the temperature is raised to 100-120°C under an inert atmosphere, and p-toluenesulfonic acid is added, and the reaction is carried out for 2-4 hours to obtain an intermediate; the temperature is lowered to 70-90°C, and a mixture of polyethylene glycol glycidyl ether and polypropylene glycol glycidyl ether and triethylamine are added, and the mixture is mixed evenly, and the reaction is carried out for 3-5 hours; the temperature is lowered to 60-80°C, and leaf alcohol and azobisisobutyronitrile are added and mixed evenly, and the reaction is carried out for 2-3.5 hours; butyl maleate is then added and mixed evenly, and the reaction is carried out for 2.5-4 hours; the temperature is lowered, washed, dried, and distilled to obtain a zwitterionic surfactant with a comb-shaped structure; The monomer A is at least one of 2,6-diaminopyridine and 1-(3-aminopropyl)imidazole; The molar ratio of the oleic acid to the monomer A is 1:(1-1.2).

[0025] Preferably, the total amount of polyethylene glycol glycidyl ether and polypropylene glycol glycidyl ether is 60% to 80% of the mass of oleic acid.

[0026] Preferably, the mass ratio of the polyethylene glycol glycidyl ether to the polypropylene glycol glycidyl ether is 1.2-1.5:1.

[0027] Preferably, the amount of leaf alcohol used is 12% to 18% of the mass of oleic acid, and the molar ratio of monobutyl maleate to leaf alcohol is (0.9 to 1.1):1.

[0028] The amount of p-toluenesulfonic acid used is 1% to 3% of the total mass of oleic acid and monomer A.

[0029] The amount of triethylamine used is 0.5% to 1.5% of the total mass of polyethylene glycol glycidyl ether and polypropylene glycol glycidyl ether.

[0030] The amount of azobisisobutyronitrile used is 1% to 2% of the total mass of leaf alcohol and monobutyl maleate.

[0031] The antioxidant is butylated hydroxyanisole, and the amount of butylated hydroxyanisole is 0.5% to 1% of the total mass of oleic acid and monomer A.

[0032] By adopting the above technical solutions, the unique comb-shaped structure gives the zwitterionic surfactant molecules multiple lipophilic and hydrophilic regions, which helps them to better adsorb and spread on the oil-water interface, thereby improving their interfacial activity. The zwitterionic properties allow it to flexibly adjust the ionization balance according to different pH environments, and maintain good solubility and surface activity under acidic, alkaline and neutral conditions, greatly broadening the application scenarios.

[0033] The zwitterionic surfactant structure can effectively resist the erosion of acidic substances (such as cyclohexane acid) and sulfides (such as hydrogen sulfide, mercaptan, etc.) in high-sulfur and high-acid crude oil, ensuring that the demulsifier can function stably and effectively in harsh environments. It works in synergy with other demulsifying components such as modified polyethers, adsorbs on the oil-water interface, and strengthens the stability and strength of the interfacial film. At the same time, it can also adjust the charge distribution at the oil-water interface, effectively promote the aggregation and separation of oil droplets and water droplets, and improve the demulsification efficiency of high-sulfur and high-acid crude oil.

[0034] Preferably, the activated alumina undergoes the following pretreatment steps before use: Mix ethyl orthosilicate, ethanol and water evenly, adjust the pH to 2-3, heat to 35-55°C, react for 3-8 hours, cool to obtain silica sol, add activated alumina and mix evenly, let stand for 16-24 hours, separate the solid and liquid, place at room temperature, age, dry and calcine to obtain.

[0035] Preferably, the volume ratio of tetraethyl orthosilicate, ethanol and water is 1:2-4:2-4; the mass ratio of activated alumina to silica sol is 1:3-5.

[0036] By adopting the above technical scheme, on the one hand, the activated alumina pretreated with silica sol has abundant surface active sites, which can not only enhance its adsorption of sulfides and acidic substances, but also produce strong physical and chemical adsorption of emulsifiers (such as asphaltene and colloid) in crude oil emulsion, thereby effectively destroying the originally stable emulsifier layer, reducing the repulsive force between oil droplets and water droplets, and facilitating the gradual aggregation of water droplets, thereby enhancing the demulsification effect. On the other hand, more hydrophilic groups (such as silanol groups) are introduced into the surface of activated alumina pretreated with silica sol. The presence of these hydrophilic groups makes the activated alumina show stronger hydrophilicity in the oil-water emulsion system. When water droplets contact these hydrophilic surfaces, they are more likely to spread out and form a thin water film. As more water droplets spread and fuse on the surface of pretreated activated alumina, the water film gradually thickens. When the gravity of the water film exceeds other forces (such as adhesion, surface tension, etc.), the water droplets will fall off the surface of the activated alumina and enter the water phase. This process not only realizes the effective separation of oil phase and water phase, but also achieves the purpose of demulsification.

[0037] Preferably, 2 to 5 parts by mass of molecular sieves are added together with the activated alumina.

[0038] Preferably, the molecular sieve is subjected to the following pretreatment steps before use: (1) Add the molecular sieve to the copper nitrate solution, mix evenly, heat to 40-60°C, mix for 18-24 hours, separate the solid and liquid, wash, and dry to obtain a preliminarily treated molecular sieve; (2) Mix ethyl orthosilicate, ethanol and water evenly, adjust the pH to 2-3, heat to 35-55°C, react for 3-8 hours, cool to obtain silica sol, add preliminary treated molecular sieve, mix evenly at room temperature, let stand for 16-24 hours, separate solid and liquid, leave at room temperature, dry, and calcine to obtain preliminary coated molecular sieve; (3) Add the preliminarily coated molecular sieve to the polyethylene glycol solution, mix evenly, raise the temperature to 45-65°C, mix for 6-8 hours, separate the solid and liquid, wash, and dry to obtain.

[0039] Preferably, the volume ratio of tetraethyl orthosilicate, ethanol and water is 1:2-4:2-4; Preferably, the concentration of the copper nitrate solution is 0.2-0.4 mol / L; the concentration of the polyethylene glycol solution is 6%-8%; the mass volume ratio of the molecular sieve, copper nitrate solution, silica sol and polyethylene glycol solution is 1 g: 10-15 ml: 4-6 g: 10-12 ml.

[0040] Preferably, the molecular weight distribution of polyethylene glycol is 2000-6000.

[0041] Preferably, the molecular sieve is ZSM-5 molecular sieve.

[0042] Preferably, the particle size distribution of the ZSM-5 molecular sieve is 3-5 μm.

[0043] By adopting the above technical solution, first, copper nitrate is used to preliminarily treat the molecular sieve. On the one hand, it enhances the adsorption active sites of the molecular sieve, greatly improving the adsorption capacity of the molecular sieve for acidic substances and sulfides in crude oil, which helps to destroy the stability of the oil-water interface and lay a good foundation for the subsequent demulsification process. On the other hand, the introduction of copper ions changes the charge distribution on the surface of the molecular sieve, making it more conducive to interacting with charged particles or polar molecules in crude oil, thereby improving the adsorption and aggregation efficiency of emulsified droplets and accelerating the overall demulsification process.

[0044] Secondly, the use of silica sol coating can form a protective film on the surface of the molecular sieve, which not only reduces the probability of active sites being poisoned or blocked, ensuring the activity and stability of the molecular sieve for a long time, but also enhances the hydrophilicity of the molecular sieve, helps to destroy the water layer structure between oil droplets, increases the chances of oil droplets colliding and coalescing with each other, promotes oil-water separation, and improves demulsification efficiency.

[0045] Finally, polyethylene glycol is coated on the surface of the molecular sieve with improved hydrophilicity. On the one hand, it can not only effectively isolate the molecular sieve structure from excessive erosion by acidic substances and sulfides, maintain the stability of the molecular sieve structure, and thus ensure the long-term stability of the demulsification performance; it can also form a certain steric hindrance on the surface of the molecular sieve to prevent excessive aggregation of particles, so that the molecular sieve is more evenly distributed on the oil-water interface, and improve the coverage and action efficiency of the emulsion droplets; in addition, polyethylene glycol can also fine-tune the hydrophilicity and hydrophobicity of the molecular sieve, so that the molecular sieve maintains sufficient hydrophilicity to promote demulsification while avoiding the adverse effects of excessive hydrophilicity, such as loss in the aqueous phase and dissolution of copper ions, which helps to reduce the risk of water pollution and achieve a green and efficient demulsification process.

[0046] Preferably, the demulsifier is compounded with polyacrylamide, and the amount of the polyacrylamide used is 2% to 4% of the mass of the demulsifier.

[0047] Preferably, the demulsifier and polyacrylamide are added in sequence with an interval of 25 to 35 minutes.

[0048] Preferably, the polyacrylamide is cationic polyacrylamide.

[0049] By adopting the above technical solution, the compound addition of polyacrylamide, during the demulsification process, on the one hand, polyacrylamide can effectively adsorb small water droplets and solid impurities in crude oil, such as silt, suspended matter, etc. This adsorption effect not only helps to purify crude oil, but also promotes small water droplets to gradually coalesce into large water droplets, thereby accelerating the separation between oil and water. On the other hand, polyacrylamide can also form a stable structure at the oil-water interface, which can prevent the separated oil and water from mixing again, that is, prevent the emulsion from re-emulsifying, and maintain the durability of the demulsification effect. In addition, in a complex crude oil system, due to the diverse components and large viscosity differences, demulsifiers are often difficult to distribute evenly. The addition of polyacrylamide can improve the fluidity of the system, making it easier for the demulsifier to diffuse and distribute in the crude oil, so that the demulsifier can more effectively contact and destroy the stability of the emulsion, thereby improving the demulsification efficiency.

[0050] In summary, this application has the following beneficial effects: 1. This application adopts modified polyether and zwitterionic surfactants, and compounded with antacids, corrosion inhibitors and activated alumina to form a multifunctional demulsification and purification system. Aiming at the complex characteristics of high-sulfur and high-acid crude oil, it makes efforts in demulsification, acid resistance, corrosion inhibition, adsorption and purification, etc., to achieve efficient demulsification and purification of crude oil, and ensure the quality and stability of the front end of the crude oil processing industry chain.

[0051] 2. In this application, it is preferred to use modified polyether and zwitterionic surfactants both with comb-shaped structures, the side chains of which can interweave and cooperate with each other at the oil-water interface to form a more compact and orderly interface film. In addition, the molecules with comb-shaped structures can be more deeply inserted into the oil phase and the water phase by virtue of their multiple side chains, and interact with the complex components in the crude oil (such as asphaltenes, colloids, etc.), thereby helping to destroy the stable structure of the high-sulfur and high-acid crude oil emulsion, making it easier to separate into oil and water phases, thereby improving the demulsification effect.

[0052] 3. The present application preferably uses silica sol to coat the activated alumina to improve the chemical stability, adsorption performance and dispersion performance of the activated alumina, and more comprehensively and effectively adsorb the acidic substances, sulfides and emulsifiers (such as asphaltene and colloid) in high-sulfur and high-acid crude oil, reduce the influence of acidic substances and sulfides on the oil-water interfacial tension of the demulsifier, and at the same time destroy the originally stable emulsifier layer to enhance the demulsification effect. DETAILED DESCRIPTION

[0053] The present application is further described in detail below with reference to embodiments.

[0054] Unless otherwise specified, the raw materials used in the examples and comparative examples of the present application are all commercially available.

[0055] Silicone rubber defoamer was purchased from Dongguan Defeng Defoamer Co., Ltd.; Cationic polyacrylamide was purchased from Gongyi Yiyang Water Treatment Materials Co., Ltd.; Activated alumina was purchased from Hebei Yuehan Metal Materials Sales Co., Ltd.; 2,6-Diaminopyridine was purchased from Nantong Runfeng Petrochemical Co., Ltd.; 1-(3-Aminopropyl)imidazole was purchased from Hubei Xingdongcheng Chemical Co., Ltd.

[0056] Preparation Examples 1-3 Modified Polyether Preparation Example 1 S11: Under nitrogen atmosphere, 20g of diethylenetriamine, 2g of potassium hydroxide and 100g of toluene were added to a reactor equipped with a stirrer, a thermometer and a pressure gauge, stirring was started at a speed of 500r / min, and after uniform mixing, the temperature was raised to 110°C at a rate of 5°C / min, and the pressure was controlled between 0.2 and 0.4MPa. 10g of propylene oxide was added to the reactor in equal amounts in 6 times, with an interval of 15min between each addition. After each addition, the reaction was maintained for 20min; then 30g of ethylene oxide was introduced into the reactor at a rate of 0.5 to 1g / min. After the introduction was completed, after the reaction for 90min, 10g of propylene oxide was added in equal amounts in 4 times. into the reactor, with an interval of 15 minutes between each addition, and after each addition, keep the reaction for 15 minutes; then, introduce 30g of ethylene oxide into the reactor, and control the introduction rate at 1-1.5g / min. After the introduction is completed, heat it to 120°C, and control the pressure between 0.3-0.5MPa, and react for 70min. After the reaction is completed, first naturally cool to room temperature, distill at 100°C and pressure between 0.03-0.05MPa for 120min, and then add deionized water of 50% of the total mass of the product, stir well, stand and separate, take the organic phase, repeat 3 times, and filter with a 0.5μm filter membrane to obtain a polyether intermediate with a comb-shaped structure; S12: Under nitrogen atmosphere, add the polyether intermediate and 50g toluene into the reactor, start stirring at a speed of 400r / min, then add 3.15g triethylamine, continue stirring for 15min, slowly add 5g allyl sultone, control the dropping time between 30 and 40min, stir and mix for 15min, heat to 90℃ at 5℃, react for 4h, measure the acid value of the product, continue to react for 30min, measure the acid value of the product again, stop the reaction when the acid value no longer changes, cool naturally to room temperature, distill at 100℃ and pressure between 0.03 and 0.05MPa for 90min, then add deionized water of 1 times the mass of the product, stir well, let stand for stratification, take the organic phase, repeat 3 times, filter with 0.5μm filter membrane to obtain modified polyether.

[0057] Among them, ethylene oxide is introduced after being liquefied, and the liquefaction temperature is 3°C.

[0058] Preparation Example 2 S11: Under nitrogen atmosphere, 10g of diethylenetriamine, 5g of triethylenetetramine, 1g of potassium hydroxide and 100g of toluene were added to a reactor equipped with a stirrer, a thermometer and a pressure gauge, stirring was started at a speed of 500r / min, and after uniform mixing, the temperature was raised to 130°C at a rate of 5°C / min, and the pressure was controlled between 0.2 and 0.4MPa. 7.5g of propylene oxide was added to the reactor in equal amounts in 4 times, with an interval of 15min between each addition. After each addition, the reaction was maintained for 15min; then 35g of ethylene oxide was introduced into the reactor at a rate of 0.5 to 1g / min. After the introduction was completed, 7.5g of propylene oxide was added in equal amounts in 4 times. Add equal amounts to the reactor twice, with an interval of 15 minutes between each addition. After each addition, keep the reaction for 10 minutes; then introduce 35g of ethylene oxide into the reactor, and control the introduction rate at 1-1.5g / min. After the introduction is completed, heat it to 140°C, and control the pressure between 0.3-0.5MPa, and react for 50 minutes. After the reaction is completed, first cool it naturally to room temperature, distill it at 100°C and a pressure between 0.03-0.05MPa for 120 minutes, and then add deionized water of 50% of the total mass of the product. After sufficient stirring, let it stand for stratification, take the organic phase, repeat 3 times, and filter it with a 0.5μm filter membrane to obtain a polyether intermediate with a comb-shaped structure; S12: Under nitrogen atmosphere, add the polyether intermediate and 50g toluene into the reactor, start stirring at a speed of 400r / min, then add 1.15g triethylamine, continue stirring for 15min, slowly add 15g allyl sultone dropwise, control the dropping time between 20 and 25min, stir and mix for 15min, heat to 110°C at 5°C / min, react for 2h, measure the acid value of the product, continue to react for 40min, measure the acid value of the product again, stop the reaction when the acid value no longer changes, cool naturally to room temperature, distill at 100°C and a pressure between 0.03 and 0.05MPa for 90min, then add deionized water 1 times the mass of the product, stir well, let stand for stratification, take the organic phase, repeat 3 times, filter with a 0.5μm filter membrane to obtain the modified polyether.

[0059] Among them, ethylene oxide is introduced after being liquefied, and the liquefaction temperature is 3°C.

[0060] Preparation Example 3 S11: Under nitrogen atmosphere, 10g of diethylenetriamine, 8g of triethylenetetramine, 1.5g of potassium hydroxide and 100g of toluene were added to a reactor equipped with a stirrer, a thermometer and a pressure gauge, stirring was started at a speed of 500r / min, and after uniform mixing, the temperature was raised to 120°C at a rate of 5°C / min, and the pressure was controlled between 0.2 and 0.4MPa. 8.5g of propylene oxide was added to the reactor in equal amounts in 5 times, with an interval of 10min between each addition. After each addition, the reaction was maintained for 18min; then 32.5g of ethylene oxide was introduced into the reactor, and the introduction rate was controlled at 0.5-1g / min. After the introduction was completed, 8.5g of propylene oxide was added after the reaction for 80min. Add equal amounts to the reactor in three times, with an interval of 15 minutes between each addition. After each addition, keep the reaction for 13 minutes; then introduce 32.5g of ethylene oxide into the reactor, and control the introduction rate at 1-1.5g / min. After the introduction is completed, heat it to 130°C, and control the pressure between 0.3-0.5MPa, and react for 60 minutes. After the reaction is completed, first cool it naturally to room temperature, distill it at 100°C and a pressure between 0.03-0.05MPa for 120 minutes, and then add deionized water of 50% of the total mass of the product. After sufficient stirring, stand for stratification, take the organic phase, repeat 3 times, and filter it with a 0.5μm filter membrane to obtain a polyether intermediate with a comb-shaped structure; S12: Under nitrogen atmosphere, add the polyether intermediate and 50g toluene into the reactor, start stirring at a speed of 400r / min, then add 2.2g triethylamine, continue stirring for 15min, slowly add 10g allyl sultone, control the dropping time between 15 and 20min, stir and mix for 15min, heat to 100℃ at 5℃ / min, react for 3h, measure the acid value of the product, continue to react for 30min, measure the acid value of the product again, stop the reaction when the acid value no longer changes, cool naturally to room temperature, distill at 100℃ and pressure between 0.03 and 0.05MPa for 90min, then add deionized water of 1 times the mass of the product, stir well, let stand for stratification, take the organic phase, repeat 3 times, filter with 0.5μm filter membrane to obtain modified polyether.

[0061] Among them, ethylene oxide is introduced after being liquefied, and the liquefaction temperature is 3°C.

[0062] Preparation Examples 4 to 6 Zwitterionic Surfactants Preparation Example 4 28.2 g of oleic acid, 10.9 g of 2,6-diaminopyridine, 100 g of toluene and 0.4 g of butylated hydroxyanisole were added to a reactor equipped with a stirrer and a thermometer, stirring was started at a speed of 300 r / min, stirring and mixing for 20 min, slowly heated to 100 ° C in a nitrogen atmosphere, and 1.2 g of p-toluenesulfonic acid was added dropwise, and the reaction was performed for 4 h to obtain an intermediate; the temperature was lowered to 70 ° C, and a mixture of 9.2 g of polyethylene glycol glycidyl ether and 7.7 g of polypropylene glycol glycidyl ether and 0.25 g of triethylamine were slowly added dropwise under stirring. After the addition was completed, the reaction was performed for 5 h, the temperature was lowered to 60 ° C, and a mixture of 1.2 g of p-toluenesulfonic acid and 0.25 g of triethylamine were added dropwise. Add 3.4g of leaf alcohol and 0.17g of azobisisobutyronitrile, react for 3.5h, then add 5.3g of monobutyl maleate, mix well, continue to react for 4h, cool naturally to room temperature, add 60% of the product mass of water and 40% of the product mass of ethanol, then adjust the pH to neutral with 10% mass fraction of sodium hydroxide, then transfer to a separatory funnel, let stand to separate, take the organic phase and dry it with anhydrous sodium sulfate, filter to remove the desiccant, and then distill at 70℃ and pressure between 3~4kPa for 2h to obtain a zwitterionic surfactant with a comb-shaped structure.

[0063] Among them, the molar mass of oleic acid is 282 g / mol, and the amount used is 0.1 mol; the molar mass of 2,6-diaminopyridine is 109 g / mol, and the amount used is 0.1 mol; the molar mass of leaf alcohol is 100 g / mol, and the amount used is 0.034 mol; the molar mass of monobutyl maleate is 172 g / mol, and the amount used is 0.031 mol.

[0064] Preparation Example 5 28.2 g of oleic acid, 8.7 g of 2,6-diaminopyridine, 5 g of 1-(3-aminopropyl)imidazole, 100 g of toluene and 0.2 g of butylated hydroxyanisole were added to a reactor equipped with a stirrer and a thermometer, stirring was started at a speed of 300 r / min, stirring and mixing for 20 min, and slowly heated to 120°C under a nitrogen atmosphere, and 0.4 g of p-toluenesulfonic acid was added dropwise, and the reaction was performed for 2 h to obtain an intermediate; the temperature was lowered to 90°C, and a mixture of 13.5 g of polyethylene glycol glycidyl ether and 9.0 g of polypropylene glycol glycidyl ether and 0.11 g of triethylamine were slowly added dropwise under stirring. After the addition was completed, the reaction was performed for 3 h, and the temperature was lowered to 80 ℃, add 5.1g leaf alcohol and 0.15g azobisisobutyronitrile, react for 2h, then add 9.6g monobutyl maleate, mix well, continue to react for 4h, cool naturally to room temperature, add 60% water of the product mass and 40% ethanol of the product mass, then adjust the pH to neutral with 10% sodium hydroxide, then transfer to a separatory funnel, let stand and stratify, take the organic phase and dry it with anhydrous sodium sulfate, filter to remove the desiccant, and then distill at 70℃ and pressure between 3~4kPa for 2h to obtain a zwitterionic surfactant with a comb-shaped structure.

[0065] Among them, the molar mass of oleic acid is 282g / mol, and the dosage is 0.1mol; the molar mass of 2,6-diaminopyridine is 109g / mol, and the dosage is 0.08mol; the molar mass of 1-(3-aminopropyl)imidazole is 125g / mol, and the dosage is 0.04mol; the molar mass of leaf alcohol is 100g / mol, and the dosage is 0.051mol; the molar mass of monobutyl maleate is 172g / mol, and the dosage is 0.056mol.

[0066] Preparation Example 6 28.2 g of oleic acid, 5.5 g of 2,6-diaminopyridine, 7.5 g of 1-(3-aminopropyl)imidazole, 100 g of toluene and 0.32 g of butylated hydroxyanisole were added to a reactor equipped with a stirrer and a thermometer, stirring was started at a speed of 300 r / min, stirring and mixing for 20 min, and slowly heated to 110°C under a nitrogen atmosphere, and 0.8 g of p-toluenesulfonic acid was added dropwise, and the reaction was carried out for 3 h to obtain an intermediate; the temperature was lowered to 80°C, and a mixture of 11.2 g of polyethylene glycol glycidyl ether and 8.6 g of polypropylene glycol glycidyl ether and 0.2 g of triethylamine were slowly added dropwise under stirring. After the addition was completed, the reaction was carried out for 4 h, and the temperature was lowered to 70 ℃, add 4.5g leaf alcohol and 0.18g azobisisobutyronitrile, react for 3h, then add 7.7g monobutyl maleate, mix well, continue to react for 3h, cool naturally to room temperature, add 60% water of the product mass and 40% ethanol of the product mass, then adjust the pH to neutral with 10% sodium hydroxide, then transfer to a separatory funnel, let stand and stratify, take the organic phase and dry it with anhydrous sodium sulfate, filter to remove the desiccant, and then distill at 70℃ and pressure between 3~4kPa for 2h to obtain a zwitterionic surfactant with a comb-shaped structure.

[0067] Among them, the molar mass of oleic acid is 282g / mol, and the dosage is 0.1mol; the molar mass of 2,6-diaminopyridine is 109g / mol, and the dosage is 0.05mol; the molar mass of 1-(3-aminopropyl)imidazole is 125g / mol, and the dosage is 0.06mol; the molar mass of leaf alcohol is 100g / mol, and the dosage is 0.045mol; the molar mass of monobutyl maleate is 172g / mol, and the dosage is 0.045mol.

[0068] Example 1 This embodiment provides a method for preparing a high-sulfur and high-acid crude oil demulsifier, comprising the following steps: At 30°C, add 40g of modified polyether and 25g of zwitterionic surfactant to a reactor equipped with a stirrer, a thermometer, and a reflux condenser, start stirring at a speed of 300r / min, stir and mix for 15min, slowly add 10g of toluene, continue stirring and mixing for 20min, then heat to 50°C, first add 3g of activated alumina and stir and mix evenly, then add 5g of ethanolamine, 3g of zinc oxide and 2g of oleic acid imidazoline, stir and mix for 40min, finally add 0.5g of silicone rubber defoamer, adjust the stirring speed to 200r / min, continue stirring and mixing for 10min, cool naturally to room temperature, transfer the reaction product to a separatory funnel, let stand for stratification, take the upper clear liquid, filter, and obtain a demulsifier.

[0069] The particle size distribution of zinc oxide is 50-100 nm; before adding zinc oxide, 15 ml of sodium dodecylbenzene sulfonate with a mass fraction of 1% is used to stir and mix the zinc oxide evenly; The particle size distribution of the activated alumina is 1-10 μm; before adding the activated alumina, 15 ml of sodium dodecylbenzene sulfonate with a mass fraction of 1% is stirred and mixed with the activated alumina.

[0070] The modified polyether is from Preparation Example 1; the zwitterionic surfactant is from Preparation Example 4.

[0071] Example 2 This embodiment provides a method for preparing a high-sulfur and high-acid crude oil demulsifier, comprising the following steps: At 40°C, add 60g of modified polyether and 30g of zwitterionic surfactant to a reactor equipped with a stirrer, a thermometer, and a reflux condenser, start stirring at a speed of 300r / min, stir and mix for 15min, slowly add 12g of toluene, continue stirring and mixing for 20min, then heat to 70°C, first add 8g of activated alumina and stir and mix evenly, then add 10g of ethanolamine, 6g of zinc oxide and 4g of oleic acid imidazoline, stir and mix for 40min, finally add 1g of silicone rubber defoamer, adjust the stirring speed to 200r / min, continue stirring and mixing for 10min, cool naturally to room temperature, transfer the reaction product to a separatory funnel, let stand for stratification, take the upper clear liquid, filter, and obtain a demulsifier.

[0072] The particle size distribution of zinc oxide is 50-100 nm; before adding zinc oxide, 25 ml of sodium dodecylbenzene sulfonate with a mass fraction of 1% is used to stir and mix the zinc oxide evenly; The particle size distribution of activated alumina is 1~10μm; before adding activated alumina, it undergoes the following pretreatment steps: 5 ml of ethyl orthosilicate, 20 ml of ethanol and 40 ml of water were mixed evenly, and the pH value was adjusted to between 2 and 3 with 10% by mass dilute hydrochloric acid, and the temperature was raised to 35°C, and the reaction was continued with stirring for 8 hours, and then the temperature was lowered to obtain a silica sol; Take 30g of silica sol, add 10g of activated alumina and mix well, let stand for 16h, filter, place at room temperature for 12h, age at 50℃ for 4h, dry, and calcine at 400℃ with a heating rate of 5~10℃ / min for 4h to obtain; The modified polyether is from Preparation Example 1; the zwitterionic surfactant is from Preparation Example 4.

[0073] Example 3 This embodiment provides a method for preparing a high-sulfur and high-acid crude oil demulsifier, comprising the following steps: At 35°C, 50g of modified polyether and 28g of zwitterionic surfactant were added to a reactor equipped with a stirrer, a thermometer, and a reflux condenser. Stirring was started at a speed of 300r / min. Stirring and mixing were performed for 15min. 10g of toluene was slowly added. Stirring and mixing were continued for 20min. The temperature was raised to 60°C. 6g of activated alumina was first added and stirred evenly. Then 7g of ethanolamine, 4g of zinc oxide, and 3g of oleic acid imidazoline were added and stirred for 40min. Finally, 0.8g of silicone rubber defoamer was added and the stirring speed was adjusted to 200r / min. Stirring and mixing were continued for 10min. The mixture was naturally cooled to room temperature. The reaction product was transferred to a separatory funnel, allowed to stand for stratification, the supernatant was taken and filtered to obtain a demulsifier.

[0074] The particle size distribution of zinc oxide is 50-100 nm; before adding zinc oxide, 15 ml of sodium dodecylbenzene sulfonate with a mass fraction of 1% is used to stir and mix the zinc oxide evenly; The particle size distribution of activated alumina is 1~10μm; before adding activated alumina, it undergoes the following pretreatment steps: 5 ml of ethyl orthosilicate, 40 ml of ethanol and 20 ml of water were mixed evenly, and the pH value was adjusted to between 2 and 3 with 10% by mass dilute hydrochloric acid, and the temperature was raised to 55°C, and the reaction was continued with stirring for 3 hours, and then the temperature was lowered to obtain a silica sol; Take 50g of silica sol, add 10g of activated alumina and mix well, let stand for 24h, filter, place at room temperature for 12h, age at 50℃ for 6h, dry, and calcine at 500℃ with a heating rate of 5~10℃ / min for 2h to obtain; The modified polyether is from Preparation Example 1; the zwitterionic surfactant is from Preparation Example 4.

[0075] Example 4 The difference between this embodiment and embodiment 3 is that: The particle size distribution of activated alumina is 1~10μm; before adding activated alumina, it undergoes the following pretreatment steps: 5 ml of ethyl orthosilicate, 30 ml of ethanol and 30 ml of water were mixed evenly, and the pH value was adjusted to between 2 and 3 with 10% by mass dilute hydrochloric acid, and the temperature was raised to 45°C, and the reaction was continued with stirring for 4.5 hours, and then the temperature was lowered to obtain a silica sol; Take 40g of silica sol, add 10g of activated alumina and mix well, let stand for 20h, filter, place at room temperature for 12h, age at 50℃ for 5h, dry, and calcine at 450℃ with a heating rate of 5~10℃ / min for 3h to obtain; The modified polyether is from Preparation Example 2; the zwitterionic surfactant is from Preparation Example 5.

[0076] The rest is the same as in Example 3.

[0077] Example 5 The difference between this embodiment and embodiment 4 is that: The modified polyether is from Preparation Example 3; the zwitterionic surfactant is from Preparation Example 6.

[0078] The rest is the same as Example 4.

[0079] Example 6 The difference between this embodiment and embodiment 5 is that: When adding activated alumina, 2 g of ZSM-5 molecular sieve was also added. Before use, the molecular sieve was pretreated as follows: (1) Add 5 g ZSM-5 molecular sieve to 50 ml 0.2 mol / L copper nitrate solution, mix well, heat to 40 °C, stir and mix for 24 h at a speed of 150 r / min, filter, rinse twice with 10 °C deionized water, each time with 10 ml, and dry at 60 °C to constant weight to obtain a preliminarily treated molecular sieve; (2) Mix 5 ml of ethyl orthosilicate, 20 ml of ethanol and 40 ml of water, adjust the pH to 2-3, heat to 35 °C, react for 8 hours, and obtain silica sol; take 40 g of silica sol and add it to the preliminarily treated molecular sieve, stir and mix for 60 minutes at room temperature, let stand for 16 hours, filter, let stand at room temperature for 12 hours, dry to constant weight at 60 °C, and then sinter at 400 °C for 4 hours, cool to obtain the preliminarily coated molecular sieve; (3) Add the preliminarily coated molecular sieve into 50 ml of 6% polyethylene glycol solution, mix well, heat to 45 °C, stir and mix for 8 h, filter, rinse twice with 20 °C deionized water, each time using 10 ml, and dry at 50 °C to constant weight.

[0080] The rest is the same as Example 5.

[0081] Example 7 The difference between this embodiment and embodiment 5 is that: When adding activated alumina, 5 g of ZSM-5 molecular sieve was also added. Before use, the molecular sieve was pretreated as follows: (1) Add 5 g ZSM-5 molecular sieve to 75 ml 0.4 mol / L copper nitrate solution, mix well, heat to 60 ° C, stir and mix for 18 h at a speed of 150 r / min, filter, rinse twice with 10 ° C deionized water, each time with 10 ml, and dry at 60 ° C to constant weight to obtain a preliminarily treated molecular sieve; (2) Mix 5 ml of ethyl orthosilicate, 40 ml of ethanol and 20 ml of water, adjust the pH to 2-3, heat to 55 °C, react for 3 h, and obtain silica sol; take 60 g of silica sol and add it to the preliminarily treated molecular sieve, stir and mix for 60 min at room temperature, let stand for 24 h, filter, let stand at room temperature for 12 h, dry to constant weight at 60 °C, and then sinter at 500 °C for 3 h, cool to obtain the preliminarily coated molecular sieve; (3) Add the preliminarily coated molecular sieve into 60 ml of 8% polyethylene glycol solution, mix well, heat to 65°C, stir and mix for 6 h, filter, rinse twice with 20°C deionized water, each time using 10 ml, and dry at 50°C to constant weight.

[0082] The rest is the same as Example 5.

[0083] Example 8 The difference between this embodiment and embodiment 5 is that: When adding activated alumina, 4 g of ZSM-5 molecular sieve was also added. Before use, the molecular sieve was subjected to the following pretreatment steps: (1) Add 5 g ZSM-5 molecular sieve to 60 ml 0.3 mol / L copper nitrate solution, mix well, heat to 50 °C, stir and mix for 20 h at a speed of 150 r / min, filter, rinse twice with 10 °C deionized water, each time with 10 ml, and dry at 60 °C to constant weight to obtain a preliminarily treated molecular sieve; (2) Mix 5 ml of ethyl orthosilicate, 30 ml of ethanol and 30 ml of water, adjust the pH to 2-3, heat to 45 °C, react for 4.5 hours to obtain silica sol; take 50 g of silica sol and add it to the preliminarily treated molecular sieve, stir and mix for 60 minutes at room temperature, let it stand for 20 hours, filter, let it stand at room temperature for 12 hours, dry to constant weight at 60 °C, and then sinter at 450 °C for 3.5 hours, cool down to obtain the preliminarily coated molecular sieve; (3) Add the preliminarily coated molecular sieve into 50 ml of 7% polyethylene glycol solution, mix well, heat to 55°C, stir and mix for 7 h, filter, rinse twice with 20°C deionized water, each time using 10 ml, and dry at 50°C to constant weight.

[0084] The rest is the same as Example 5.

[0085] Comparative Example 1 The difference between this comparative example and Example 1 is: The modified polyether is a common polyether, and the preparation method of the common polyether comprises the following steps: S11: Under a nitrogen atmosphere, 20 g of diethylenetriamine, 2 g of potassium hydroxide and 100 g of toluene are added to a reactor equipped with a stirrer, a thermometer and a pressure gauge, and stirring is started at a speed of 500 r / min. After mixing evenly, the temperature is raised to 110°C at a rate of 5°C / min, and the pressure is controlled between 0.4 and 0.6 MPa. First, 20 g of propylene oxide is added to the reactor at a rate of 2 to 3 g / min, and then 60 g of ethylene oxide is added to the reactor at a rate of 3 to 4 g / min. After reacting for 4 hours, it is naturally cooled to room temperature, and distilled at 100°C and a pressure between 0.03 and 0.05 MPa for 120 minutes, and then 50% of the total mass of the product is added with deionized water. After sufficient stirring, the mixture is allowed to stand for stratification, and the organic phase is taken. After repeating 3 times, it is filtered using a 0.5 μm filter membrane to obtain a polyether intermediate; S12: Under nitrogen atmosphere, add the polyether intermediate and 50g toluene into the reactor, start stirring at a speed of 400r / min, then add 3.15g triethylamine, continue stirring for 15min, slowly drop 5g allyl sultone, control the dropping time between 30 and 40min, stir and mix for 15min, raise the temperature to 90℃ at 5℃, react for 4h, measure the acid value of the product, continue to react for 30min, measure the acid value of the product again, stop the reaction when the acid value no longer changes, cool naturally to room temperature, distill at 100℃ and a pressure between 0.03 and 0.05MPa for 90min, then add deionized water of 1 times the mass of the product, stir well, let stand for stratification, take the organic phase, repeat 3 times, filter with a 0.5μm filter membrane to obtain ordinary polyether.

[0086] Among them, ethylene oxide is introduced after being liquefied, and the liquefaction temperature is 3°C.

[0087] The rest is the same as in Example 1.

[0088] Comparative Example 2 The preparation method of the modified polyether comprises the following steps: Under nitrogen atmosphere, 20g of diethylenetriamine, 2g of potassium hydroxide and 100g of toluene were added to a reactor equipped with a stirrer, a thermometer and a pressure gauge, stirring was started at a speed of 500r / min, and after uniform mixing, the temperature was raised to 110°C at a rate of 5°C / min, and the pressure was controlled between 0.2 and 0.4MPa. 10g of propylene oxide was added to the reactor in 6 equal amounts, with an interval of 15min between each addition. After each addition, the reaction was maintained for 20min; then 30g of ethylene oxide was introduced into the reactor, and the introduction rate was controlled at 0.5-1g / min. After the introduction was completed, after the reaction for 90min, 10g of propylene oxide was added in 4 equal amounts. 1.5 g of ethylene oxide was added into the reactor at an interval of 15 min between each addition. After each addition, the reaction was maintained for 15 min. Then 30 g of ethylene oxide was introduced into the reactor at a rate of 1-1.5 g / min. After the introduction was completed, the temperature was raised to 120°C and the pressure was controlled between 0.3 and 0.5 MPa. The reaction was carried out for 70 min. After the reaction was completed, the reactor was naturally cooled to room temperature, and distilled at 100°C and a pressure between 0.03 and 0.05 MPa for 120 min. Then, 50% of the total mass of the product was added with deionized water. After sufficient stirring, the reactor was allowed to stand for stratification. The organic phase was taken and repeated 3 times. The modified polyether was obtained by filtering with a 0.5 μm filter membrane.

[0089] The rest is the same as in Example 1.

[0090] Comparative Example 3 The difference between this comparative example and Example 1 is: The preparation method of zwitterionic surfactant comprises the following steps: 28.2 g of oleic acid, 10.5 g of diethanolamine, 100 g of toluene and 0.4 g of butylated hydroxyanisole were added to a reactor equipped with a stirrer and a thermometer, stirring was started at a speed of 300 r / min, stirring and mixing for 20 min, and slowly heated to 100 ° C in a nitrogen atmosphere, and 1.2 g of p-toluenesulfonic acid was added dropwise, and the reaction was performed for 4 h to obtain an intermediate; the temperature was lowered to 70 ° C, and a mixture of 9.2 g of polyethylene glycol glycidyl ether and 7.7 g of polypropylene glycol glycidyl ether and 0.25 g of triethylamine were slowly added dropwise under stirring. After the addition was completed, the reaction was performed for 5 h, and the temperature was lowered to 6 At 0℃, add 3.4g leaf alcohol and 0.17g azobisisobutyronitrile, react for 3.5h, then add 5.3g monobutyl maleate, mix well, continue to react for 4h, cool naturally to room temperature, add 60% water and 40% ethanol of the product mass, then adjust the pH to neutral with 10% sodium hydroxide, then transfer to a separatory funnel, let stand to separate, take the organic phase and dry it with anhydrous sodium sulfate, filter to remove the desiccant, and then distill at 70℃ and pressure between 3~4kPa for 2h to obtain a zwitterionic surfactant with a comb-shaped structure.

[0091] Among them, the molar mass of oleic acid is 282 g / mol, and the amount used is 0.1 mol; the molar mass of diethanolamine is 105 g / mol, and the amount used is 0.1 mol; the molar mass of leaf alcohol is 100 g / mol, and the amount used is 0.034 mol; the molar mass of monobutyl maleate is 172 g / mol, and the amount used is 0.031 mol.

[0092] The rest is the same as in Example 1.

[0093] Comparative Example 4 The difference between this comparative example and Example 1 is: The preparation method of zwitterionic surfactant comprises the following steps: 28.2g oleic acid, 10.9g 2,6-diaminopyridine, 100g toluene and 0.4g butyl hydroxyanisole were added to a reactor equipped with a stirrer and a thermometer, stirring was started at a speed of 300r / min, stirring and mixing for 20min, slowly heated to 100°C under a nitrogen atmosphere, 1.2g p-toluenesulfonic acid was added dropwise, and the mixture was reacted for 4h to obtain an intermediate; the temperature was lowered to 60°C, 3.4g leaf alcohol and 0.17g azobisisobutyronitrile were added, the mixture was reacted for 3.5h, and then 5.3g monobutyl maleate was added, mixed evenly, and the reaction was continued for 4h, and then naturally cooled to room temperature, 60% water of the product mass and 40% ethanol of the product mass were added, and then the pH was adjusted to neutral with 10% sodium hydroxide by mass, and then the mixture was transferred to a separatory funnel, allowed to stand for stratification, the organic phase was dried with anhydrous sodium sulfate, the desiccant was filtered out, and then distilled at 70°C and a pressure between 3 and 4kPa for 2h to obtain a zwitterionic surfactant.

[0094] Among them, the molar mass of oleic acid is 282 g / mol, and the amount used is 0.1 mol; the molar mass of 2,6-diaminopyridine is 109 g / mol, and the amount used is 0.1 mol; the molar mass of leaf alcohol is 100 g / mol, and the amount used is 0.034 mol; the molar mass of monobutyl maleate is 172 g / mol, and the amount used is 0.031 mol.

[0095] The rest is the same as in Example 1.

[0096] Performance Testing Test raw materials: Qilu Petrochemical Shengli Refinery, a high-sulfur and high-acid crude oil, the sulfur content is about 2.7%, the mercaptan content is moderate, thiophene and its derivatives account for a high proportion, the acid value is about 1.9mgKOH / g, mainly cyclohexane acid, among which asphaltene, colloid and other heavy components account for about 30.8%, and the density is about 0.935g / cm at 20℃. 3 , the water content is about 29.6%.

[0097] (1) Detection 1 At 20°C, 12 samples were prepared from the above high-sulfur and high-acid crude oil, which were marked as samples 1 to 12 in sequence. The amount of high-sulfur and high-acid crude oil used in each sample was 200g. The demulsifiers prepared in Examples 1 to 8 and Comparative Examples 1 to 4 were added at a dosage of 30ppm, and then stirred and mixed at a speed of 300r / min. 30ml of samples were taken at specified time intervals and transferred to centrifuge tubes. The centrifuge tubes were placed in a centrifuge and centrifuged at 3000r / min for 15min to fully separate the oil phase and the water phase. After the separation was completed, the volume of the lower water phase was measured, and the water density was calculated based on the water density of 1g / cm 3 , calculate the water quality, and then calculate the dehydration rate. The results are shown in Table 1.

[0098] Table 1 Performance test data of demulsifiers prepared in Examples 1 to 8 and Comparative Examples 1 to 4

[0099] (2) Test 2 At 20°C, take the above high-sulfur and high-acid crude oil to prepare two samples, marked as sample 13 and sample 14 respectively. The amount of high-sulfur and high-acid crude oil in each sample is 200g. After adding the demulsifier prepared in Example 7 at a dosage of 30ppm, stir and mix at a speed of 300r / min for about 25-30min, then add cationic polyacrylamide accounting for 2% of the amount of demulsifier and cationic polyacrylamide accounting for 4% of the amount of demulsifier respectively, stir and mix evenly, take 30ml samples at the specified time intervals, and transfer them to centrifuge tubes. Put the centrifuge tube into a centrifuge and centrifuge at 3000r / min for 15min to fully separate the oil phase and the water phase. After the separation is completed, measure the volume of the lower water phase and calculate the volume according to the water density 1g / cm 3 , calculate the water quality, and then calculate the dehydration rate. The results are shown in Table 2.

[0100] Table 2 Performance test data after compounding Example 7 with cationic polyacrylamide

[0101] (3) Test three For sample 7 corresponding to Example 7 in test 1 and sample 13 corresponding to Example 7 in test 2, after settling and dehydration for 90 minutes, the separated oil phases were tested for sulfur content and acid value. The test results are shown in Table 3.

[0102] Table 3 Sulfur content and acid value test data in the oil phase of sample 7 and sample 13

[0103] The performance test data of the demulsifiers prepared from Examples 1 to 8 and Comparative Examples 1 to 4 are shown in Table 1: First, the modified polyether with a comb-shaped structure and the zwitterionic surfactant with a comb-shaped structure can quickly and effectively promote the aggregation of tiny water droplets, so that the water phase can be initially separated from the oil phase. Its interaction with other components in the crude oil can not only reduce the stabilizing effect of these components on the emulsification, but also form a more stable adsorption layer at the oil-water interface, preventing the separated water droplets from returning to the oil phase, greatly improving the dehydration rate in the crude oil.

[0104] Secondly, by pre-treating the activated alumina, the dispersion and adsorption properties of the activated alumina in the crude oil system are improved, which effectively destroys the originally stable emulsifier layer, thereby enhancing the demulsification effect.

[0105] Finally, by adding the pretreated molecular sieve, the molecular sieve can quickly adsorb small molecular impurities in the crude oil system, freeing up effective action space at the oil-water interface for the demulsifier, thereby further improving the dehydration rate in the crude oil.

[0106] By analyzing the data in Table 2, it can be seen that when cationic polyacrylamide is used in combination with the demulsifier in Example 7, the cationic polyacrylamide begins to play a flocculation role in the early stage, so that the water droplets separated by the demulsifier can aggregate and settle faster, preventing the emulsion from re-emulsifying, thereby improving the overall dehydration efficiency.

[0107] By analyzing the data in Table 3, it can be seen that the demulsifier prepared in Example 7 can effectively reduce the sulfur content and acid value in the crude oil system while demulsifying. This is the result of the demulsification effect of the demulsifier itself and the synergistic effect of components such as cationic polyacrylamide. These mechanisms of action cooperate with each other to achieve the improvement of crude oil quality, providing favorable conditions for subsequent crude oil processing and product quality improvement.

[0108] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. A method for preparing a high-sulfur and high-acid crude oil demulsifier, characterized in that: The steps include: 40-60 parts by weight of modified polyether, 25-30 parts by weight of zwitterionic surfactant and 10-12 parts by weight of solvent are mixed evenly, heated to 50-70° C., 3-8 parts by weight of activated alumina, 8-16 parts by weight of antacid and 2-4 parts by weight of corrosion inhibitor are added, mixed evenly, 0.5-1 parts by weight of defoamer are added, mixed evenly, cooled, and allowed to stand for stratification to obtain a demulsifier; Such antacids include ethanolamine and zinc oxide.

2. The method for preparing a high-sulfur and high-acid crude oil demulsifier according to claim 1, characterized in that: The preparation method of the modified polyether comprises the following steps: S11: Under an inert atmosphere, polyethylene polyamine, catalyst A and solvent are mixed uniformly in a reactor, and the temperature is raised to 110-130° C., and then a portion of propylene oxide is added to the reactor in 4-6 times, and each time it is added, the reaction is carried out for 15-20 minutes; then a portion of ethylene oxide is added to the reactor, and the reaction is carried out for 60-90 minutes, and another portion of propylene oxide is added to the reactor in 2-4 times, and each time it is added, the reaction is carried out for 10-15 minutes, and then another portion of ethylene oxide is added to the reactor, and the temperature is raised to 120-140° C., and after reacting for 50-70 minutes, the temperature is lowered, distilled, and washed to obtain a polyether intermediate with a comb-shaped structure; S12: Under an inert atmosphere, the polyether intermediate, catalyst B, solvent and allyl sultone are uniformly mixed in a reactor, the temperature is raised to 90-110° C., the reaction is performed for 2-4 hours, the temperature is lowered, distilled and washed to obtain a modified polyether; The mass ratio of the polyethylene polyamine, propylene oxide and ethylene oxide is (15-20): (15-20): (60-70); the amount of the allyl sultone is 5%-15% of the total mass of the polyethylene polyamine, propylene oxide and ethylene oxide.

3. The method for preparing the high-sulfur and high-acid crude oil demulsifier according to claim 2, characterized in that: The polyethylene polyamine is at least one of diethylenetriamine and triethylenetetramine.

4. The method for preparing a high-sulfur and high-acid crude oil demulsifier according to claim 1, characterized in that: The preparation method of the zwitterionic surfactant comprises the following steps: The oleic acid, monomer A, solvent and antioxidant are mixed evenly, and the temperature is raised to 100-120°C under an inert atmosphere, and p-toluenesulfonic acid is added, and the reaction is carried out for 2-4 hours to obtain an intermediate; the temperature is lowered to 70-90°C, and a mixture of polyethylene glycol glycidyl ether and polypropylene glycol glycidyl ether and triethylamine are added, and the mixture is mixed evenly, and the reaction is carried out for 3-5 hours; the temperature is lowered to 60-80°C, and leaf alcohol and azobisisobutyronitrile are added and mixed evenly, and the reaction is carried out for 2-3.5 hours; butyl maleate is then added and mixed evenly, and the reaction is carried out for 2.5-4 hours; the temperature is lowered, washed, dried, and distilled to obtain a zwitterionic surfactant with a comb-shaped structure; The monomer A is at least one of 2,6-diaminopyridine and 1-(3-aminopropyl)imidazole; The molar ratio of the oleic acid to the monomer A is 1:(1-1.2).

5. The method for preparing the high-sulfur and high-acid crude oil demulsifier according to claim 4, characterized in that: The total amount of the polyethylene glycol glycidyl ether and the polypropylene glycol glycidyl ether is 60% to 80% of the mass of the oleic acid.

6. The method for preparing a high-sulfur and high-acid crude oil demulsifier according to claim 1, characterized in that: Before use, the activated alumina undergoes the following pretreatment steps: Mix ethyl orthosilicate, ethanol and water evenly, adjust the pH to 2-3, heat to 35-55°C, react for 3-8 hours, cool to obtain silica sol, add activated alumina and mix evenly, let stand for 16-24 hours, separate the solid and liquid, place at room temperature, age, dry and calcine to obtain.

7. The method for preparing a high-sulfur and high-acid crude oil demulsifier according to claim 1, characterized in that: When adding activated alumina, 2 to 5 parts by mass of molecular sieves are also added.

8. The method for preparing a high-sulfur and high-acid crude oil demulsifier according to claim 7, characterized in that: Before use, the molecular sieve undergoes the following pretreatment steps: (1) Add the molecular sieve to the copper nitrate solution, mix evenly, heat to 40-60°C, mix for 18-24 hours, separate the solid and liquid, wash, and dry to obtain a preliminarily treated molecular sieve; (2) Mix ethyl orthosilicate, ethanol and water evenly, adjust the pH to 2-3, heat to 35-55°C, react for 3-8 hours, cool to obtain silica sol, add preliminary treated molecular sieve, mix evenly at room temperature, let stand for 16-24 hours, separate solid and liquid, leave at room temperature, dry, and calcine to obtain preliminary coated molecular sieve; (3) Add the preliminarily coated molecular sieve to the polyethylene glycol solution, mix evenly, raise the temperature to 45-65°C, mix for 6-8 hours, separate the solid and liquid, wash, and dry to obtain.

9. The method for preparing a high-sulfur and high-acid crude oil demulsifier according to claim 1, characterized in that: The corrosion inhibitor is imidazoline oleate.

10. The method for preparing a high-sulfur and high-acid crude oil demulsifier according to claim 1, characterized in that: The demulsifier is compounded with polyacrylamide, and the amount of the polyacrylamide used is 2% to 4% of the mass of the demulsifier.

Citation Information

Patent Citations

  • Composite demulsifying agent

    CN103374386A

  • Acid-containing crude oil demulsifying agent and preparation method thereof

    CN102140365A

  • Demulsifier for oilfield sewage, and preparation method thereof

    CN110921773A

  • Composite demulsifier and preparation process thereof

    CN113684053A

  • Novel demulsifier

    US20220213244A1

Cited By

  • Selective desulfurization and decarburization agent and preparation method thereof

    CN120860793A

  • Demulsifier based on modified polyether as well as preparation method and application of demulsifier

    CN121360397A

  • A demulsifier based on modified polyether, its preparation method and application

    CN121360397B